2019
DOI: 10.24014/ekl.v2i1.7560
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Praktik Kerja Industri Terhadap Kesiapan Kerja Siswa Kelas XII SMK Kartini Sintang

Abstract: Penelitian ini bertujuan untuk mengetahui pengaruh praktik kerja industri terhadap kesiapan kerja siswa kelas XII SMK Kartini Sintang Tahun Pelajaran 2017/2018. Metode yang digunakan adalah kuantitatif dan bentuk penelitian yang digunakan adalah eksplanasi survei. Berdasarkan hasil penelitian terhadap 40 responden yang diteliti, diperoleh nilai praktik kerja industri diperoleh rata-rata hitung (Mean) 86,88, median (Me) 86,50, modus (Mode) 85 dan Standart Deviasi 4,127, praktik kerja industri termasuk kategori … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…According to [5] in his research, he concluded that the implementation of internship in the field of computer network engineering had a positive impact on the work readiness of vocational students in Pekan Baru, this was because through internships it could not only provide provisions in the form of hard skills in the form of increased abilities and knowledge but also soft skills in the form of forming attitude, sense of responsibility and recognize the work environment. The same thing is also concluded in quantitative research by [6] stating that there is a significant influence between industrial work practices on students' work readiness with the t-value of 3,242.…”
Section: Introductionmentioning
confidence: 54%
“…According to [5] in his research, he concluded that the implementation of internship in the field of computer network engineering had a positive impact on the work readiness of vocational students in Pekan Baru, this was because through internships it could not only provide provisions in the form of hard skills in the form of increased abilities and knowledge but also soft skills in the form of forming attitude, sense of responsibility and recognize the work environment. The same thing is also concluded in quantitative research by [6] stating that there is a significant influence between industrial work practices on students' work readiness with the t-value of 3,242.…”
Section: Introductionmentioning
confidence: 54%